2015
DOI: 10.1088/0741-3335/57/5/054010
|View full text |Cite
|
Sign up to set email alerts
|

Investigating profile stiffness and critical gradients in shaped TCV discharges using local gyrokinetic simulations of turbulent transport

Abstract: Abstract. The experimental observation made on the TCV tokamak of a significant confinement improvement in plasmas with negative triangularity ( δ < 0) compared to those with standard positive triangularity has been interpreted in terms of different degrees of profile stiffness (Sauter et al. Phys. Plasmas 21 055906, 2014) and/or different critical gradients. Employing the Eulerian gyrokinetic code GENE (Jenko et al. Phys. Plasmas 7 1904, 2000, profile stiffness and critical gradients are studied under TCV re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(75 citation statements)
references
References 17 publications
23
52
0
Order By: Relevance
“…Finally, since TCV is a small-sized tokamak, it is expected that finite ρ effects could lead to a significant discrepancy between local flux-tube results and global ones [19] (ρ ∼ 1/100 at ρ tor = 0.6). Previous turbulent transport studies of TCV discharges using flux-tube models, addressing internal transport barriers [21] and plasma shaping effects [20] have pointed out the importance of these effects. This will involve carrying out simulations using the global version of the GENE code.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, since TCV is a small-sized tokamak, it is expected that finite ρ effects could lead to a significant discrepancy between local flux-tube results and global ones [19] (ρ ∼ 1/100 at ρ tor = 0.6). Previous turbulent transport studies of TCV discharges using flux-tube models, addressing internal transport barriers [21] and plasma shaping effects [20] have pointed out the importance of these effects. This will involve carrying out simulations using the global version of the GENE code.…”
Section: Discussionmentioning
confidence: 99%
“…The results presented in this paper are limited to local simulations, even though finite machine size effects requiring so-called global simulations are known to be important in smaller size tokamaks like TCV [19][20][21]. It has indeed been shown that important properties of such smaller systems can be understood by performing simpler local simulations [20]. After this first step, we plan in the future to also carry out global GENE simulations.…”
Section: Introductionmentioning
confidence: 99%
“…The focus of this paper is indeed on qualitatively reproducing the experimental observations regarding the spatial nature of axisymmetric fluctuations. We have in particular investigated the effect of finite collisionaly, a parameter know to have a strong impact on turbulence in TCV relevant conditions [28] and in general affecting the dynamics of zonal flows, and of the safety factor profile. A quantitative investigation, aiming at reproducing both the experimental transport and fluctuation level, will likely require not only to adopt the realistic deuterium-to-electron mass ratio but also to include impurities which are known to potentially strongly affect the turbulence level [28] as well as the linear GAM frequency [7].…”
Section: Numerical Simulation Toolmentioning
confidence: 99%
“…Other non-linear simulations performed using the GENE code [11], on the same experimental proles and equilibria, again found TEM dominated uctuations, reproduced the heat ux dierence at the plasma edge and suggested that, to reproduce the penetration of the heat ux reduction in the plasma core, global simulations would be necessary. Moreover, indications were found that changing triangularity from positive to negative increases the critical electron temperature gradients for the saturated heat ux [7] number radiative temperature uctuations. It exploits cross-correlation analysis on close but not overlapping plasma volumes to detect small uctuations (<1%).…”
Section: Introductionmentioning
confidence: 99%